Quantum Dots in Nanotechnology: Advances in Therapeutics, Drugs Delivery and Imaging - Yamuna, Buchaiahgaripalli; Bharath Kumar, Vepamani Siva Sai; Ismael, Kateregga; Mahammed, Nawaz; Reddy, Sabbella Sameera; Shahid, Sunkesula; Sowmya, Gangaigari; Reddy, Lingala Tharun Kumar; Kumar, Bellam Raj (International Journal of Pharmaceutical Investigation, 2025)
Quantum Dots (QDs), semiconductor nanoparticles, exhibit unique optical properties like excellent photostability, high brightness, and size-tuneable emission wavelengths due to quantum confinement. Their broad absorption and narrow emission spectra make them ideal for high-resolution, multicoloured imaging in biological and medical applications. QDs are increasingly used in cellular, molecular, and in vivo imaging, as well as diagnostic techniques for cancer and pathogen detection. Additionally, they hold promise for targeted drug delivery, where surface functionalization with biomolecules allows precise targeting. However, concerns about QD toxicity, influenced by surface coatings and size, remain. Research into biocompatible coatings is essential to address safety concerns. Future advancements in QD synthesis, functionalization, and integration with nanotechnologies will further enhance their potential in personalized medicine. Overcoming regulatory and safety challenges is critical for their clinical adoption.
Keywords: Biocompatible coatings; Drug delivery; Multicoloured imaging; Nanomedicine; Quantum dots